Women in Marvel films - Kent, Miriam (Edinburgh University Press, 2021)
"The concept of identity in superhero narratives has become a burgeoning field in academic studies of this increasingly popular cinematic genre. Women in Marvel Films provides the first rigorous analysis of the portrayals of women, heroic and otherwise, in films based on Marvel comics from the 1980s to the present. It explores the relationships between this cultural phenomenon and wider issues of gender equality, considering the cultural moments in which Marvel films are made and incorporating complex histories of the comic book and Hollywood industries. The book also asks how feminist issues surface within superhero adaptations and how they are dealt with via Hollywood and comic book conventions. Women in Marvel Films shows how the Marvel superhero film taps into political complexities regarding gender and related identity issues, such as women's roles in society and their relation to men, and provides a fascinating insight into gendered power dynamics in contemporary American popular culture."--